Genotyping by RAD sequencing enables mapping of fatty acid composition traits in perennial ryegrass (Lolium perenne (L.)). Issue 5 (18th January 2013) - Hegarty, Matthew; Yadav, Rattan; Lee, Michael; Armstead, Ian; Sanderson, Ruth; Scollan, Nigel; Powell, Wayne; Skøt, Leif
Summary Perennial ryegrass (Lolium perenne L.) is the most important forage crop in temperate livestock agriculture. Its nutritional quality has significant impact on the quality of meat and milk for human consumption. Evidence suggests that higher energy content in forage can assist in reducing greenhouse gas emissions from ruminants. Increasing the fatty acid content (especially α‐linolenic acid, an omega‐3 fatty acid) may thus contribute to better forage, but little is known about the genetic basis of variation for this trait. To this end, quantitative trait loci (QTLs) were identified associated with major fatty acid content in perennial ryegrass using a population derived from a cross between the heterozygous and outbreeding high‐sugar grass variety AberMagic and an older variety, Aurora. A genetic map with 434 restriction‐associated DNA (RAD) and SSR markers was generated. Significant QTLs for the content of palmitic (C16:0) on linkage groups (LGs) 2 and 7; stearic (C18:0) on LGs 3, 4 and 7; linoleic (C18:2n‐6) on LGs 2 and 5; and α‐linolenic acids (C18:3n‐3) on LG 1 were identified. Two candidate genes (a lipase and a beta‐ketoacyl CoA synthase), both associated with C16:0, and separately with C18:2n‐6 and C18:0 contents, were identified. The physical positions of these genes in rice and their genetic positions in perennial ryegrass were consistent with established syntenic relationships between these two species. Validation of these associations is required, but the utility of RAD markers for rapid generation of genetic maps and QTL analysis has been demonstrated for fatty acid composition in a global forage crop.